PREVALENCE AND AWARENESS OF TEXT NECK SYNDROME & ADDICTION TO SMARTPHONES IN DOCTOR OF PHYSICAL THERAPY STUDENTS OF PESHAWAR - Khattak, Shamaal; Gul, Mashal; Kakar, Hoor Ali; Ullah, Ghazanfar; Rahman, Mujeeb Ur (Annals of Allied Health Sciences, 2020)
OBJECTIVE: To determine the prevalence of text neck syndrome in Doctor of Physical Therapy students, their addiction level to smart phones and awareness regarding text neck syndrome. METHODS: This cross-sectional survey was conducted on Doctor of Physical therapy students studying in constituent and affiliated institutes of Khyber Medical University Hayatabad, Peshawar. Data was collected from 299 participants recruited through systematic random sampling. SPSS version 20 was used for data analysis. RESULTS: Out of 299 participants, 76 (25.4%) had text neck syndrome while 223 (74.6%) had no text neck syndrome. Regarding awareness of text neck syndrome, 79(26.4%) were aware of text neck syndrome, 101(33.8%) have heard about it but don’t know what it is, while 119(39.8%) were not aware of the text neck syndrome. The calculated addiction rate of our population was found to be 117.03. CONCLUSION: About one fourth of the students (25.4%) were suffering from text neck pain with overuse of smart phone and low level of awareness regarding it, therefore preventive measures should be taken to minimize the occurrence of text neck syndrome.